Estudo de complexos envolvendo íons lantanídeos trivalentes e ligantes orgânicos, utilizando espectroscopias de aniquilação de pósitrons e óptica - Fernando Fulgencio Henriques (2013)
This work investigated the formation of positronium (Ps) in the isolated complexes Sm(dpm)3, Eu(dpm)3, Gd(dpm)3, Tb(dpm)3, Ho(dpm)3, Er(dpm)3, and Yb(dpm)3, where dpm corresponds to the 2,2,6,6-tetramethyl-3-5-heptanedionate ion. Mechanical mixtures and binary solid solutions with general formula Ln11-xLn2x(dpm)3 were also studied, where Ln1 corresponds to the ions Sm3+, Gd3+, Tb3+, Ho3+, Er3+, Yb3+, and Ln2 corresponds to the ions Eu3+, Gd3+, and Yb3+.With the use of positron annihilation lifetime spectroscopy (PALS), Doppler broadening annihilation radiation lineshape (DBARL), Mossbauer spectroscopy, and luminescence spectroscopy, Ps formation was investigated in these systems. The goal was to obtain more information on the Ps formation process and on how certain molecular properties ¡V such as the energy of the ligand-metal charge transfer state (LMCTS) or the tendency of Ln3+ ions to capture electrons ¡V interfere on the Ps formation. PALS measurements, together with the analysis of the relative intensity of ortho-positronium formation, I3 (%), have shown that the Sm(dpm)3, Gd(dpm)3, Tb(dpm)3, Ho(dpm)3, Er(dpm)3 and Yb(dpm)3 complexes form significant amounts of Ps (I3 between 35 and 45 %), whereas the Eu(dpm)3 virtually does not form any Ps (I3 around 2.5%). PALS, Mossbauer, and luminescence measures were performed on Eu(dpm)3 at 80 and 295 K, in an attempt to verify previous assumptions that would explain the low intensity of Ps formation observed in the vast majority of Eu3+ complexes. The results suggest that the spur model (the most commonly used to explain the formation of Ps) and the intramolecular electron delocalization model do not agree with experimental data. Even though the results confirm the influence of low-energy LMCTS on the Ps formation process, the results obtained at 80 K suggest the existence of other mechanisms, currently unknown, involved in the absence of Ps formation on Eu(dpm)3.The high intensity of Ps formation on Yb(dpm)3 (I3 around 45%) was rather surprising, since the Yb3+ and Eu3+ complexes were expected to show a low I3 (%). The analysis of the Ln3+ reduction potentials (E0), the LMCTS energies of the Ln(dpm)3 complexes and the electronic configurations of the Yb3+ and Eu3+ ions were not sufficient to provide a consistent explanation. The reasons why the Yb(dpm)3 features a high Ps formation intensity, similar to the other Ln(dpm)3, are not yet well understood, and will be the subject of further studies.When studying by PALS and DBARL solid solutions and mechanical mixtures with general formula Ln11-xEux(dpm)3, it has been observed that I3 (%) decreases with the increase of Eu3+ concentration in the mechanical mixtures as well as in the solid solutions, showing that the Eu3+ ion behaves as a Ps formation inhibitor. The Sm1-xEux(dpm)3, Gd1-xEux(dpm)3, and Tb1-xEux(dpm)3 systems, originating from complexes with the same crystal structure (monoclinic dimers), formed solid solutions, clearly showing the total inhibition of Ps formation. On the other hand, PALS and DBARL results indicate the formation of mechanical mixtures in systems Ho1-xEux(dpm)3, Er1-xEux(dpm)3 and Yb1-xEux(dpm)3, since these systems consist of complexes with different crystal structures (monoclinic dimers and orthorhombic monomers).PALS measurements at 80 K were performed on Gd(dpm)3, Eu(dpm)3, Tb(dpm)3, and on solid solutions with general formula Gd1-xEux(dpm)3 and Tb1-xEux(dpm)3. Both solid solutions, as well as the isolated complexes, have shown I3 (%) obtained at 80 K that were considerably lower than the I3 (%) obtained at 295 K. Since this result does not appear to agree with the spur model, the decrease in I3 (%) was explained with a model according to which the formation of Ps would occur from the interaction between the positron and an excited electron of the ligand. The shorter the lifetime of the excited state, the less intense the interactions positron-electron will be, and the lesser the amount of Ps formed. At 80 K, the HOMO-LUMO and LUMO-HOMO transitions are favored due to the more rigid symmetry of the system, reducing the lifetime of the electron in the excited state, and therefore reducing the amount of PS formed.From luminescence measurements performed on the Tb1-xEux(dpm)3 solid solutions, we obtained a linear correlation between the 5D4 excited level lifetime of the Tb3+ ion and I3 (%): both of them decrease when Eu3+ concentration, xEu, increases in the system. This correlation cannot be explained by the spur model. Therefore, a kinetic mechanism was proposed which involves the participation of the ligand¡¦s excited states in the Ps formation. According to this mechanism, the Tb3+ ³ Eu3+ energy transfer and the dpm ³ Eu(dpm)3 charge transfer processes account for the lifetime reduction of the ligand¡¦s excited state, L*Tb, and of the excited Tb3+, LTb*, causing the inhibition of Ps formation and the luminescence suppression. An equation was then deduced which correlates the I3 (%) with the lifetime of level 5D4 of the Tb3+, which satisfactorily fitted the experimental data (I3 as a function of xEu). By applying the kinetic mechanism to the Gd1-xEux(dpm)3 system, where there is no energy transfer from dpm to Gd3+, or from Gd3+ to Eu3+, we were able to deduce an equation rather similar to the Stern-Volmer equation correlating I3 (%) and xEu. The obtainment of experimental evidence suggesting the participation of excited states in the formation of Ps is an original result that opens a new line of research in the area of positron annihilation. In face of the results obtained, it would be interesting to develop new experiments that could provide additional evidence supporting the proposed kinetic mechanism.